Luminescence Sensitisation of Natural Quartz Using Pre-Exposure Dose and Thermal Activation Techniques (2014)
Luminescence sensitisation is an important stage in the application of quartz in pre-dose retrospective dosimetry and dating. The existing techniques for sensitisation in quartz are Pre-Exposure Dose (PED) and Thermal Activation (TA). Previous works were centred on combined actions of PED and TA with less attention given to the separate contributions of these techniques in pre-dose sensitisation of quartz. This work was undertaken to determine the separate contributions of PED and TA in sensitisations of 110oC Thermoluminescence (TL) peak and Room Temperature Linearly Modulated Optically Stimulated Luminescence (RT-LMOSL) of quartz. Two sets of quartz samples, one from Oro in Kwara State (S2) and the other from Ijero-Ekiti, Ekiti State (S4) with high sensitisation signals were used. Each of the two sets was divided into two parts; the first was unannealed while the second part was annealed, following standard procedures. Each of the unannealed and annealed samples was further divided into 38 aliquots required for the protocol. Fourteen aliquots each of unannealed and annealed samples were given PED and another set of 14 aliquots were without PED. The TL and RT-LMOSL measurements were carried out on each aliquot using an automated (model-TL/OSL–DA–15). Sensitisation reproducibility of repeated TL measurements on 10 different aliquots of each of the unannealed and annealed samples was quantified using Coefficient of Variation (CV). Data were analysed using descriptive statistics. reader TL/OSL RISØThe sensitisation signals of the aliquots of unannealed samples without PED was higher than that of the aliquots with PED by factor of 76.0 % and 79.0 % for TL and RT-LMOSL respectively for S2 while the corresponding factors obtained for S4 were 45.0 % for TL and 14.0 % for RT-LMOSL. In annealed samples, the sensitisation signal of the aliquots with PED was rather higher than that of the aliquots without PED, by factor of 224.0 % for TL and 201.0 % for RT-LMOSL for S2 and for S4, it was by factor of 245.0 % for TL and 217.0 % for RT-LMOSL. The sensitisations reproducibility of aliquots of unannealed samples were found to be poor with CV of 33.5 % for S2 and 52.0 % for S4. This improved significantly in the annealed samples to CV 6.3 % for S2 and 9.0 % for S4. Luminescence sensitisation by pre-exposure dose was dominant in annealed quartz samples. Therefore, only annealed quartz samples are recommended for pre-dose retrospective dosimetry and dating. The use of 110oC thermoluminescence peak signal in sensitisation corrections of unannealed quartz is not advisable.